Cyber harassment of children with special reference to digital games - Baltezarević Vesna; Baltezarević Radoslav; Baltezarević Ivana (Temida, 2023)
Children in the modern environment are increasingly becoming active users of digital technologies. In a digital environment, they communicate with their peers, watch video content or have fun playing digital games. However, their inexperience can often expose them to malicious activities from other Internet users, such as cyber-harassment. Cyberbullies can be individuals or groups that use audio and/ or visual content to single out a child as a target for abusive and harassing behaviour (for various reasons). Such activities can have long-term consequences for children (anxiety, depression, low self-esteem, suicidal thoughts), especially if they last for a long period of time, and if the children do not see a way out of such a situation. Parents have certainly been identified as the first line of defence against cyberbullying. By talking about children‘s digital activities, playing digital games together, and constantly monitoring children‘s behaviour in the digital environment, it is possible to detect the problem in time and protect children‘s digital safety. Also, companies that produce digital games, with the development of adequate software, and initiatives that punish the disturbing behaviour of cyber bullies, but also praise the fair and sporting behaviour of other users, contribute to suppressing such phenomena. The subject of this article refers to the analysis, identification and prevention of cyber harassment to which children are exposed in the virtual environment, especially while interacting with other players in the process of playing digital games. The aim of the paper is to point out the problem of cyber harassment of children and to let the general public know that more attention must be paid to this problem.